Zur Edition einer Inschrift des Assyrerkönigs Tukulti-Ninurta I. - Görg, Manfred (Biblische Notizen, 2009)
The newly presented studies concerning the “Great Inscription of Tukuti-Ninurta I from his New Palace in Assur” by M.P. Streck (in WdO) do nor offer a new edition of the whole inscription but give further important philological and semantic explications together with corrections of readings that are to some extent well known, added to the first presentation of the extensive inscription (ed. by M. Görg).